Proses Penalaran Matematis Siswa SMP dalam Statistika - Saminanto, Saminanto; Suwarno, Muji; Septianah, Septianah; Aistafania, Aistafania (Square : Journal of Mathematics and Mathematics Education, 2024)
Mathematical reasoning is very important for students to master. This research aims to reveal students' mathematical reasoning processes in solving statistical problems. This research used a descriptive qualitative method involving 25 students from class VII-D of SMP Negeri 16 Semarang. The research instrument consists of mathematical problems related to statistics. Data collection was carried out through written tests and interviews. Data were analyzed by data reduction, data presentation, and drawing conclusions. The research results showed that 16% of students had high mathematical reasoning abilities, 72% of students had moderate mathematical reasoning abilities, and 12% of students had low mathematical reasoning abilities. Based on the results of interviews, the mathematical reasoning process of lower group students is hampered by the process of presenting mathematical statements verbally, drawings, sketches or diagrams; make allegations; checking the validity of an argument; and students' lack of understanding of mathematical concepts. The implications of the findings in this research can be used as a reference for developing appropriate learning strategies to overcome students' difficulties in the mathematical reasoning process. Keywords: reasoning process, mathematics, statistics.